Study on the First Attack Probability by Close Air Support - Dong Wenhong, Gao Yu, Wang Lei, Han Yulong (Editorial Office of Aero Weaponry, 2021)
With the upgrading of air defense weapons, the significance of improving the first attack probability by close air support is increasingly prominent. It is directly related to the safety of combat aircraft, and related to the success of the support mission. In this paper, by analyzing the basic combat process of close air support, the first attack probability of close air support is studied by analytical method, and the first attack probability model of close air support is given.